The treatment of impending and existing pathological femoral fractures using the long gamma nail. - Edwards, SA; Pandit, H; Clarke, H (2001)
The subtrochanteric region of the femur accounts for one-third of all pathological fractures requiring surgical intervention. The large forces occurring in this region and the possible non-occurrence of bony consolidation constitute a difficult problem to the trauma surgeon. The medical records and X-rays of 25 consecutive patients treated with the long gamma nail (LGN) for pathological (impending or existing) fractures of the femur were analysed retrospectively. Our results in the use of the LGN for pathological fractures of the femur have been good. We recommend an aggressive approach to the early stabilisation of impending fractures and the use of distal locking.